Taekwondo Coach Image, Career Satisfaction and Continuous Sports Engagement: Empirical Evidence from Luoyang, China - Mengnan Xie; Fuyuan Sun , (Revista de Psicología del Deporte (Journal of Sport Psychology), 2023)
The purpose of this study is to examine the relationship between the psychological elements of participants' participation satisfaction, sports engagement, and intention for continued participation. The participants in Luoyang City, Henan Province, who practice Taekwondo were selected for the questionnaire. For exploratory factor analysis, correlation analysis, and multiple regression analysis, SPSS statistical software is utilized. The results indicate that the image aspects, attributes, accountability, professionalism, and professional awareness of Taekwondo teachers have a substantial impact on participant satisfaction. This study showed that if coaches have work duties, work skills and abilities, as well as self-management, students' sports participation will increase and their interest will increase. Moreover, this study concludes that involvement satisfaction has a considerable beneficial effect on the intention to continue participating. Likewise, sports participation has a considerable beneficial effect on the intention to continue participating.